Regional enteritis (Crohn’s disease) - J. Pollero, Hector (Cirugía del Uruguay, 1971)
The paper contains a brief ·description of the main radiologic characteristics of Crohn's disease in its different localizations in the digestive tube and sorne of the possible differential diagnosis.